FAKTOR-FAKTOR YANG MEMPENGARUHI INNOVATION PERFORMANCE PADA PT BANK CENTRAL ASIA PRIORITAS KCU SCBD - Kania Astri Fatiha; Netania Emilisia; Tiara Puspa; Fitriyani Fitriyani (STMIK Widuri Jakarta, 2025)
This study aims to analyze the factors influencing Innovation Performance, consisting of several predictors. The research design applies hypothesis testing to examine the effects of Deliberate Innovation Practice, Opportunity Perception, and Platform Digitization Capability on Innovation Performance among employees of BCA Prioritas branches at KCU SCBD, BEJ, Senayan City, and Santa in South Jakarta. A quantitative research approach was employed. The data analysis method used is Structural Equation Modeling (SEM) with the aid of AMOS 22 software. Prior to hypothesis testing, a goodness-of-fit test was conducted. The research findings indicate that Deliberate Innovation Practice, Opportunity Perception, and Platform Digitization Capability all have a positive influence on Innovation Performance. The novelty of this research lies in its focus on Innovation Performance within the banking sector, while previous studies have predominantly observed companies in the business and tourism sectors. Additionally, this study introduces Platform Digitization Capability as a rarely examined predictor.